Promoting Physical Activity in Women Referred to Health Centers Applying the Trans-theoretical Model - Nahid Eskandari; Marzieh Araban; Amal Saki Malehi (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Despite all its advantages, many people still engage less physical activity in their leisure time. In this context, a theory-based intervention to promote physical activity in women referred to Izeh health centers was designed. Methods: In a quasi-experimental study, a random sample of 120 women was selected and randomly assigned into experimental and control groups. A valid and reliable questionnaire including data on stages of change, benefits, barriers, self-efficacy and processes of change were used to collect the data. Data were gathered at baseline. educational intervention including lecture and group discussion was implemented for the experimental group. After 3-month follow-up, data were collected again and analyzed via SPSS16 using t test and Chi-square at the level of 0.05 significance. Results: Although before the intervention, there was no significant association between experimental group and control, after the intervention, stage transition was significant between the two groups (p0.05). Conclusion: Implementing interventional programs based on Trans-theoretical Model could improve physical activity behavior. Paper Type: Research Article.